PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KEUNGGULAN BERSAING PADA PT TOYOTA KALLA CABANG ALAUDDIN MAKASSAR - Ahmad Firman (Jurnal Bisnis dan Kewirausahaan, 2017)
This study aimed to determine the effect of TQM is measured based on customer focus, continuous improvement, education and training, and empowering employees to competitive advantage at PT. Toyota Kalla Branch Alauddin Makassar, either partially or simultaneously. The research was conducted at PT. Toyota Kalla Branch Alauddin Makassar, with a total population of 103 people. The research sample was determined by using the technique of non-probability sampling techniques slovin with a total sample of 51 employees. Analysis of the data in this study using multiple linear regression analysis. The results showed that TQM is measured based on customer focus, continuous improvement, education and training, as well as employee empowerment, partially or simultaneously significant effect on the competitive advantage in the PT. Toyota Kalla Branch Alauddin Makassar. The independent variables that have a dominant influence on competitive advantage at PT. Toyota Kalla Branch Alauddin Makassar is variable continuous improvement with the greatest Beta coefficient is 0.400.